Evaluating the Dynamics of Groundwater Storage and Its Sustainability in the Loess Plateau: The Integrated Impacts of Climate Change and Human Activities - Jifei Li; Jinzhu Ma (Remote Sensing)
In recent decades, the Loess Plateau has undergone rapid urbanization alongside extensive afforestation efforts aimed at controlling soil erosion. These large-scale land use changes have inevitably affected the region’s hydrological cycle. Despite these changes, the impact on groundwater has not been thoroughly investigated. This study aims to examine the spatial and temporal evolution of groundwater storage (GWS) in the Loess Plateau from 2003 to 2022, identify the driving factors behind these changes, and evaluate the sustainability of groundwater levels through the Reliability–Resilience–Vulnerability framework. GWS changes were estimated using GRACE gravity satellite data and the Global Land Assimilation Dataset (GLDAS). Our study also analyzed the drivers of GWS evolution by integrating land use change data, ERA5-Land reanalysis data, and various statistical data. Our findings indicate a decline in GWS at a rate of −6.9 ± 3.84 mm/yr. Seasonal variations show that the GWS is relatively higher in spring and autumn, but lower in summer and winter. The eastern part of the Loess Plateau in particular is experiencing a rate of decline that is 150% of that of the overall regional average. Groundwater storage in the Loess Plateau is currently at a critically unsustainable level, with conditions in the west being more favorable compared to the central and eastern regions. Climate factors such as precipitation, evaporation, and runoff did not show a significant correlation with GWS changes. Increases in forest areas and water consumption together explained 95.8% of the changes in GWS, with forest area growth being the dominant factor. Human activities are identified as the main cause of GWS decline. This study’s findings improve our understanding of GWS dynamics in the Loess Plateau and offer a scientific basis for formulating groundwater resource management and ecological restoration policies in the region.